Pengaruh Good Governance dan Motivasi Kerja Terhadap Kinerja Manajerial Penyelenggara Pemerintahan Desa di Kabupaten Badung - Iswara, Anak Agung Mas Prabha; Putri, I. G. A. M. Asri Dwija (E-Jurnal Akuntansi, 2019)
The aim of this research is to know how influence good governance and work motivation in managerial performance of government officials in Badung Regency. The sample of this study is 230 respondents from the village officials of Badung Regency. Determination of the sample using non-probability sampling with saturation sampling technique. To collect the data, the researcher using questionnaires and data analysis techniques using multiple linear regression analysis. The result of the data showed that Good Governance and Work Motivation variables have a positive effect on the Managerial Performance of Village Government Officials in Badung Regency. Keywords : Good Governance; Work Motivation; Managerial Performance.